Social inequality in public education during the COVID-19 pandemic: analysis of productions in the area of Education - de Souza Ribeiro, Camila; da Silva Darcoleto, Carina Alves [UNESP] (Universidade Estadual de Ponta Grossa (UEPG), 2024)
This text, based on the dialectical historical materialist theoretical and methodological framework, aims to present analysis data on how academic productions in the field of Education addressed social inequality and its impacts on Brazilian public education during the COVID-19 pandemic. It is a bibliographic and documentary research, guided by the state of knowledge. The survey and selection of material were carried out in the databases of the Journal Portal and the Catalog of Theses and Dissertations of the Coordination for the Improvement of Higher Education Personnel (CAPES), covering the period from 2020 to early 2022. The research analyzed a total of 34 articles and ten Master’s theses. To address social inequality in Brazil, in addition to a bibliography that discusses the theme, documents were used, including the report from the Continuous National Household Sample Survey (PNAD) (2021). The results indicate that the productions, when discussing education during the pandemic, point to the effects of social inequality on it, although, in general, they do not advance in discussing the relationship among the elements that constitute this inequality.
Desigualdad social en la educación pública durante la pandemia de covid-19: análisis de producciones en el área de Educación
Desigualdade social na educação pública no período da pandemia da covid-19: análise de produções da área da Educação
Keywords: COVID-19 pandemic; Education; Research in Education; Social inequality